Grade 2 and 3 Obesity and Diagnosed Prostate Cancer in Middle-Aged and Elderly Men: An Epidemiologic Study with Stratified Multistage Sampling Design. (8th January 2014) - Liu, Xuefeng; Khoury, Amal; Longcoy, Joshua; Ikekwere, Joseph
Abstract : Background . The association of obesity with the odds of diagnosed prostate cancer (DPC) is inconclusive. Whether grade 2 or grade 3 obesity is associated with increased odds of DPC has not been investigated. Design and Methods . Cross-sectional data of 7, 974 subjects aged ≥40 years were collected from the National Health and Nutrition Examination Survey 2001–2010. Odds ratios (ORs) of DPC associated with grade 2 or grade 3 obesity were estimated by conducting weighted logistic regression models. Results . The unadjusted rates of DPC did not differ significantly over grades of BMI (P = 0.7044 ). After adjustment for different groups of potential confounding factors, grade 2 or grade 3 obesity was not significantly associated with the odds of DPC with ORs changing from 0.62 to 0.69 for grade 2 obesity and from 0.81 to 1.09 for grade 3 obesity. Moreover, morbid obesity (grade 2 and 3 obesity combined) was not linked to the odds of DPC. Conclusion . Grade 2 or grade 3 obesity was not associated with the odds of DPC. Whether they are associated with a substantially increased risk of high-grade DPC needs to be further investigated as accumulating evidence has shown that obesity increases the risk of high-grade disease.